Amorphous FeP2 as well as preparation method and application thereof
Through the method of hydrothermal reaction and phosphating reaction, amorphous FeP2 is prepared by controlling the phosphating conditions, which solves the problem of volume change in FeP2 materials during the lithiation/delithiation process, and achieves low-temperature preparation and high cycle stability, avoiding the use of highly toxic gases.
Patent Information
- Application Number
- CN202411736573.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-11-29
AI Technical Summary
In the prior art, FeP2 materials have serious volume changes in the lithiation/delithiation process, resulting in poor cycle stability of the battery. At the same time, high temperature and highly toxic PH3 gas are required during the preparation process, which has safety and environmental problems.
Amorphous FeP2 is prepared by hydrothermal reaction and phosphating reaction. By controlling the supply of phosphorus source, hydrogen-argon mixed atmosphere, phosphating temperature and time, amorphous FeP2 materials are prepared by low-temperature phosphating, avoiding the use of highly toxic PH3 gas.
The low-temperature preparation of amorphous FeP2 materials is achieved, which avoids crystalline transitions caused by high temperatures, improves the structural stability and cyclic stability of the material, and avoids the use of highly toxic gases, improving the safety and environmental protection of the preparation process.
Smart Images

Figure CN119873771A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery electrode materials, and in particular to an amorphous FeP 2 And its preparation method and application. Background Art
[0002] In recent years, China has vigorously developed green new energy to replace oil and other traditional energy sources, such as solar energy, wind energy, tidal energy and nuclear energy, to reduce carbon emissions and cope with the global warming crisis. Rechargeable lithium-ion batteries (LIBs) are the driving force of new energy vehicles because they are CO2-free. 2 As one of the effective measures to reduce carbon emissions, lithium-ion batteries are large-capacity, stable-performance rechargeable batteries with low pollution, high energy density, long cycle life, high rate and other excellent properties. They have become the main direction of global energy development.
[0003] Compared with intercalation-type carbon negative electrode materials, metal phosphides can store energy through intercalation and conversion reactions and have good specific capacity. At the same time, iron and phosphorus reserves are abundant and easy to mine. Therefore, economical iron phosphide is a very promising negative electrode material for high-performance lithium-ion batteries. At present, there are six known iron phosphides: Fe 4 P, Fe 3 P, Fe 2 P, FeP, FeP 2 and FeP 4 , they have different electronic and physicochemical properties. The theoretical specific capacitance of iron phosphide increases with the increase of phosphorus content, while the conductivity decreases with the increase of phosphorus content. 2 P and FeP have been widely studied in LIBs. 2 The theoretical specific capacity is as high as 1365mAh / g, which is higher than Fe 2 P (563mAh / g) and FeP (926mAh / g), which are also much higher than the traditional graphite anode (372mAh / g). 2 The material undergoes severe volume changes during the lithiation / delithiation process, and is prone to irreversible side reactions such as material crushing, resulting in poor battery cycle stability.
[0004] Amorphous materials have the characteristics of long-range disorder, short-range order, and abundant structural defects. They are a new strategy to effectively improve the structural stability of materials. The expansion rate of amorphous materials in all directions is consistent during the process of lithium extraction / insertion, which can maintain the high strain of the material and improve the structural stability of amorphous materials; the amorphous state leads to an increase in the MP bond length and a decrease in the coordination number, and produces a large number of active sites and ion diffusion channels, accelerating ion diffusion and charge transfer. In addition, the Gibbs free energy change of the reaction between amorphous materials and Li is lower than that of the crystalline state, and the reversibility of the conversion reaction of amorphous materials is stronger. Therefore, amorphous materials show better performance in lithium battery electrodes than crystalline materials.
[0005] Compared with the amorphous phase synthesis of iron oxide or iron sulfide, amorphous FeP 2 The synthesis of nanomaterials is more difficult, and the main challenge is the low-temperature phosphating process. 2 The high temperature of the phosphating process conflicts with the low temperature of amorphous material preparation. Phosphorus vapor can be used to prepare FeP 2 Nanomaterials, but because phosphorus molecules are inert in the gas phase, the phosphating reaction requires high temperatures (>500°C). 2 The material is not suitable for high temperature preparation. Higher preparation temperature will make amorphous FeP 2 The material transforms into crystalline FeP 2 Secondly, low temperature phosphating requires a phosphorus source with high reactivity (such as PH 3 ), but PH 3 It is a highly toxic gas that will seriously endanger the life and health of scientific researchers. For the above reasons, there is no amorphous FeP 2 Low temperature preparation method of materials.
[0006] Therefore, the research has obtained an amorphous FeP with high energy density, high stability, high conductivity and small volume expansion during charge and discharge. 2 Its preparation method and application are of great significance. Summary of the invention
[0007] In view of this, the present invention provides an amorphous FeP 2 The preparation method and application thereof are aimed at solving the problems of high preparation temperature and use of highly toxic PH in the prior art. 3 Gas problem.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] The present invention provides an amorphous FeP 2 The preparation method comprises the following steps:
[0010] (1) hydrothermally reacting iron salt, urea and water to obtain an iron source precursor;
[0011] (2) The iron source precursor and the phosphorus source are subjected to a phosphating reaction in a mixed gas to obtain an amorphous FeP 2 .
[0012] Preferably, the iron salt is ferric chloride hexahydrate.
[0013] Preferably, the usage ratio of the iron salt, urea and water is 1 mol: 1-3 mol: 5-10 L.
[0014] Preferably, in step (1), the temperature of the hydrothermal reaction is 100 to 120° C., and the time of the hydrothermal reaction is 6 to 8 hours.
[0015] Preferably, in step (2), the phosphorus source is sodium hypophosphite; and the mass ratio of the iron source precursor to the phosphorus source is 1:10-25.
[0016] Preferably, in step (2), the phosphating reaction is carried out in a tubular furnace; the iron source precursor is located in the middle and downstream of the tubular furnace, the phosphorus source is located in the upstream of the tubular furnace, and the distance between the iron source precursor and the phosphorus source is 1 to 5 cm.
[0017] Preferably, in step (2), the mixed gas is a mixed gas of hydrogen and argon, the flow rate of the mixed gas is 400-500 cc / min, and the volume ratio of the hydrogen to argon is 10-20:80-90.
[0018] Preferably, in step (2), the heating rate of the phosphating reaction is 2-4°C / min, the temperature of the phosphating reaction is 200-300°C, and the time of the phosphating reaction is 4-8h.
[0019] The present invention also provides the amorphous FeP 2 The amorphous FeP prepared by the preparation method 2 .
[0020] The present invention also provides the amorphous FeP 2 Application in lithium-ion batteries.
[0021] It can be seen from the above technical solutions that, compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The present invention comprehensively regulates the parameters such as the phosphorus source supply, hydrogen-argon mixed atmosphere, phosphating temperature, and phosphating time. The hydrogen content in the mixed gas increases the activity of P in the phosphorus source, avoiding the use of highly toxic PH 3Gas is used to control the energy barrier of the phosphating reaction; the amount of P reaction is increased by the amount of phosphorus source supplied, and the supply efficiency of P atoms in the phosphating process is controlled by combining the gas flow rate and the distance between the two porcelain boats; low crystallinity phosphating is performed by using a lower heating rate, a lower phosphating temperature and a longer phosphating time to avoid the formation of crystalline materials due to excessively high phosphating temperatures, thereby realizing the preparation of amorphous FeP by low-temperature phosphating 2 Material.
[0023] (2) With crystalline FeP 2 Compared with the material, the amorphous FeP prepared by the present invention 2 The material has the following advantages:
[0024] Amorphous FeP 2 The material has a lower potential barrier, and the Gibbs free energy change between the reaction and Li is lower than that of crystalline FeP 2 Lower material, amorphous FeP 2 The reversibility of material conversion reactions is stronger;
[0025] Amorphous FeP 2 The material has abundant unsaturated coordination bonds, which provide more active sites and ion diffusion channels, which is beneficial to the diffusion and charge transfer of lithium ions;
[0026] Amorphous FeP 2 The isotropic properties of the material are conducive to maintaining high volume strain in all directions and inhibiting the amorphous FeP 2 Volume deformation of materials improves structural stability and cycle stability;
[0027] Amorphous FeP 2 The material has extremely low crystallinity, presents amorphous characteristics, and has excellent electrochemical properties. It has a high reversible specific capacity and stable cycle rate performance. 2 Provide more solutions as negative electrode materials in lithium-ion battery applications;
[0028] Amorphous FeP 2 The electrode exhibits better cycle stability and rate performance. When charged and discharged at a high current density of 2A / g, the reversible specific capacity can reach 640.5mAh / g after 1000 cycles, and the capacity loss rate is as low as 18.4%. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0030] Figure 1 Amorphous FeP obtained in Examples 1 to 2 2 Materials and Crystalline FeP Obtained in Comparative Example 1 2 XRD pattern of the material;
[0031] Figure 2 Amorphous FeP obtained in Example 1 2 SEM images of the material at different magnifications;
[0032] Figure 3 Amorphous FeP obtained in Example 1 2 CV curve of the electrode;
[0033] Figure 4 Amorphous FeP obtained in Examples 1 to 2 2 Electrode and crystalline FeP obtained in comparative example 1 2 Cycling performance diagram of the electrode;
[0034] Figure 5 Amorphous FeP obtained in Example 1 2 Electrode and crystalline FeP obtained in comparative example 1 2 Rate performance diagram of the electrode;
[0035] Figure 6 Amorphous FeP obtained in Example 1 2 Electrode and crystalline FeP obtained in comparative example 1 2 Electrochemical impedance test diagram of the electrode;
[0036] Figure 7 Amorphous FeP obtained in Example 1 2 CV curve of the electrode at a scan rate of 0.1 to 2 mV / s;
[0037] Figure 8 Amorphous FeP obtained in Example 1 2 The corresponding log(i) vs.log(v) plot of the electrode;
[0038] Fig. 9 Amorphous FeP obtained in Example 1 2 Estimation of the pseudocapacitive contribution of the electrode at a scan rate of 2.0 mV / s;
[0039] Fig.10 Amorphous FeP obtained in Example 1 2 Plot of the contribution of electrode pseudocapacitance and diffusion-controlled effects to the total charge storage. DETAILED DESCRIPTION
[0040] The present invention provides an amorphous FeP 2 The preparation method comprises the following steps:
[0041] (1) hydrothermally reacting iron salt, urea and water to obtain an iron source precursor;
[0042] (2) The iron source precursor and the phosphorus source are subjected to a phosphating reaction in a mixed gas to obtain an amorphous FeP 2 .
[0043] In the present invention, the iron salt is preferably ferric chloride hexahydrate.
[0044] In the present invention, the usage ratio of the iron salt, urea and water is preferably 1 mol: 1-3 mol: 5-10 L, more preferably 1 mol: 1.5-2.5 mol: 6-8.5 L, and more preferably 1 mol: 1.8-2 mol: 6.5-7.5 L.
[0045] In the present invention, in the step (1), the iron salt, urea and water are mixed before the hydrothermal reaction, and the mixing time is preferably 20 to 40 minutes, more preferably 25 to 35 minutes, and more preferably 30 minutes. The mixing speed is preferably 450 to 550 rpm, more preferably 460 to 520 rpm, and more preferably 480 to 500 rpm.
[0046] In the present invention, in step (1), the temperature of the hydrothermal reaction is preferably 100-120°C, more preferably 105-118°C, more preferably 110-116°C, and the time of the hydrothermal reaction is preferably 6-8h, more preferably 6.5-7.5h, more preferably 7h.
[0047] In the present invention, in the step (1), cooling, washing and drying are sequentially performed after the hydrothermal reaction; the cooling temperature is preferably 20-30°C, more preferably 22-28°C, and more preferably 24-26°C; the washing is performed by alternating deionized water and anhydrous ethanol for one wash, the number of washes is preferably 5-7 times, and more preferably 6 times; the washing is preferably centrifugal washing, the rotation speed of the centrifugal washing is preferably 4500-5500rpm, more preferably 4600-5200rpm, and more preferably 4800-5000rpm; the time for each washing with deionized water and anhydrous ethanol is preferably 8-12min, more preferably 9-11min, and more preferably 10min; the drying temperature is preferably 100-120°C, more preferably 105-115°C, and more preferably 110-112°C; the drying time is preferably 10-14h, more preferably 11-13h, and more preferably 12h.
[0048] In the present invention, in step (2), the phosphorus source is preferably sodium hypophosphite; the mass ratio of the iron source precursor to the phosphorus source is preferably 1:10-25, more preferably 1:14-20, and more preferably 1:16-20.
[0049] In the present invention, in the step (2), the phosphating reaction is carried out in a tubular furnace; the iron source precursor and the phosphorus source are respectively placed in two porcelain boats, the iron source precursor is located in the middle and downstream of the tubular furnace, and the phosphorus source is located in the upstream of the tubular furnace, and the distance between the two porcelain boats is preferably 1 to 5 cm, more preferably 2 to 4 cm, and more preferably 3 cm.
[0050] In the present invention, in the step (2), the mixed gas is preferably a mixed gas of hydrogen and argon, the flow rate of the mixed gas is preferably 400-500cc / min, more preferably 420-480cc / min, more preferably 450-460cc / min, and the volume ratio of hydrogen to argon is preferably 10-20:80-90, more preferably 12-18:82-88, more preferably 15-16:84-85.
[0051] In the present invention, in the step (2), the heating rate of the phosphating reaction is preferably 2 to 4°C / min, more preferably 2.2 to 3.5°C / min, more preferably 2.5 to 3.0°C / min, the temperature of the phosphating reaction is preferably 200 to 300°C, more preferably 230 to 290°C, more preferably 260 to 280°C, and the time of the phosphating reaction is preferably 4 to 8h, more preferably 5 to 7h, more preferably 5.5 to 6h.
[0052] The present invention also provides the amorphous FeP 2 The amorphous FeP prepared by the preparation method 2 .
[0053] The present invention also provides the amorphous FeP 2 Application in lithium-ion batteries.
[0054] In the present invention, the amorphous FeP 2 It is preferably used as an electrode in lithium-ion batteries. 2 For lithium-ion half-cells the following steps are involved:
[0055] 1) Amorphous FeP 2 , acetylene black, carboxymethyl cellulose and water are mixed to obtain electrode slurry;
[0056] 2) Apply the obtained electrode slurry on the surface of nickel foam and dry it to obtain amorphous FeP 2 electrode;
[0057] 3) Amorphous FeP 2 The electrode is used as the positive electrode, the lithium sheet is used as the negative electrode, Gelgard2400 is used as the separator, and 1 mol / L LiPF 6The solution is an electrolyte (the solvent is a mixed solution of ethyl carbonate, dimethyl carbonate and ethyl carbonate in a volume ratio of 1:1:1), and a CR2032 button cell is assembled in a glove box filled with argon.
[0058] In the present invention, the amorphous FeP 2 The mass ratio of acetylene black, carboxymethyl cellulose and water is preferably 8:1:1:100.
[0059] In the present invention, the loading amount of the electrode slurry on the surface of the nickel foam is preferably 0.6 to 1.4 mg / 115 cm 2 , more preferably 0.8 to 1.2 mg / 115 cm 2 , more preferably 0.9 to 1.0 mg / 115 cm 2 The drying temperature is preferably 80° C., and the drying time is preferably 12 h.
[0060] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0061] Example 1
[0062] 0.004 mol of ferric chloride hexahydrate, 0.012 mol of urea and 40 mL of deionized water were mixed at a speed of 500 rpm for 0.5 h to form a clear solution, and the clear solution was transferred into a 100 mL polytetrafluoroethylene-lined reactor, heated to 120° C. in a blower box for reaction for 6 h, cooled to 25° C., and washed alternately by centrifugation with deionized water and anhydrous ethanol, and washed 6 times with deionized water and anhydrous ethanol respectively (the speed of centrifugal washing was 5000 rpm, and the time of each centrifugation was 10 min), and dried in a blower oven at 110° C. for 12 h to obtain an iron source precursor;
[0063] Mix the iron source precursor and NaH 2 PO 2 They are placed in two porcelain boats, the porcelain boat containing the iron source precursor is located in the downstream of the tube furnace, and the NaH 2 PO 2 The porcelain boat is located upstream of the tube furnace, and the two porcelain boats are 2 cm apart. A mixed gas (hydrogen and argon volume ratio of 20:80) is introduced at a gas flow rate of 500 cc / min, and the temperature is raised to 260°C at a heating rate of 2.5°C / min. Phosphating is performed at 260°C for 4 hours to obtain amorphous FeP. 2 Material.
[0064] Example 2
[0065] The preparation steps of the iron source precursor are the same as those in Example 1;
[0066] Mix the iron source precursor and NaH 2 PO 2 They are placed in two porcelain boats, the porcelain boat containing the iron source precursor is located in the downstream of the tube furnace, and the NaH 2 PO 2 The porcelain boat is located upstream of the tube furnace, and the two porcelain boats are 3 cm apart. A mixed gas (hydrogen and argon volume ratio is 15:85) is introduced at a gas flow rate of 400 cc / min, and the temperature is raised to 280°C at a heating rate of 3°C / min. Phosphating is performed at 280°C for 4 hours to obtain amorphous FeP. 2 Material.
[0067] Comparative Example 1
[0068] The preparation steps of the iron source precursor are the same as those in Example 1;
[0069] Mix the iron source precursor and NaH 2 PO 2 They are placed in two porcelain boats, the porcelain boat containing the iron source precursor is located in the downstream of the tube furnace, and the NaH 2 PO 2 The porcelain boat is located upstream of the tube furnace, and the two porcelain boats are 2 cm apart. A mixed gas (hydrogen and argon volume ratio of 5:95) is introduced at a gas flow rate of 400 cc / min, and the temperature is increased to 500°C at a heating rate of 2.5°C / min. Phosphating is performed at 500°C for 4 hours to obtain crystalline FeP. 2 Material.
[0070] The amorphous FeP of Examples 1 to 2 2 Crystalline FeP of Materials and Comparative Example 1 2 The materials are FeP 2 The materials are assembled into batteries in the following steps and performance tests are performed:
[0071] According to the mass ratio of 8:1:1:100, FeP 2 The material, acetylene black, carboxymethyl cellulose and water are mixed to obtain an electrode slurry;
[0072] The obtained electrode slurry was coated on the surface of nickel foam (the loading amount of the electrode slurry was 1 mg / 115 cm 2 ) and then dried at 80 ° C for 12 h to obtain FeP 2 electrode;
[0073] The obtained FeP 2 The electrode is the positive electrode, the lithium sheet is the negative electrode, Gelgard2400 is the diaphragm, and 1 mol / L LiPF 6The solution is an electrolyte (the solvent is a mixed solution of ethyl carbonate, dimethyl carbonate and ethyl carbonate in a volume ratio of 1:1:1), and a CR2032 button cell is assembled in a glove box filled with argon.
[0074] Amorphous FeP obtained in Examples 1 to 2 2 Materials and Crystalline FeP Obtained in Comparative Example 1 2 The XRD pattern of the material is as follows Figure 1 As shown. Figure 1 It can be seen that the amorphous FeP obtained in Examples 1 to 2 2 The material did not show obvious characteristic diffraction peaks, while the crystalline FeP obtained in Comparative Example 1 2 The material showed obvious characteristic diffraction peaks.
[0075] Amorphous FeP obtained in Example 1 2 The CV curve of the electrode is shown in Figure 3 As shown. Figure 3 It can be seen that the amorphous FeP prepared in Example 1 2 The first three cyclic voltammetry curves of the electrode, combined with Figure 1 The XRD test results can explain the amorphous FeP 2 Lithiation / delithiation behavior of electrode materials.
[0076] Amorphous FeP obtained in Examples 1 to 2 2 Electrode and crystalline FeP obtained in comparative example 1 2 The cycling performance of the electrode is shown in Figure 2. Figure 4 As shown. Figure 4 It can be seen that after 1000 cycles of charge and discharge at a high current density of 2A / g, the FeP 2 The reversible specific capacity of the electrode is 640.5 mAh / g, and the capacity loss rate is only 18.4%. 2 The reversible specific capacity of the electrode is 574 mAh / g, and the capacity loss rate is only 21.6%. 2 The reversible specific capacity of the electrode is only 359 mAh / g.
[0077] Amorphous FeP obtained in Example 1 2 Electrode and crystalline FeP obtained in comparative example 1 2 The rate performance of the electrode is shown in the figure Figure 5 As shown. Figure 5 It can be seen that the amorphous FeP obtained in Example 1 2 The electrode is compared with the crystalline FeP obtained in Comparative Example 1. 2 The electrode exhibits excellent cycle stability and rate performance.
[0078] Amorphous FeP obtained in Example 1 2Electrode and crystalline FeP obtained in comparative example 1 2 Electrochemical impedance test of the electrode Figure 6 As shown. Figure 6 It can be seen that the amorphous FeP obtained in Example 1 2 The semicircle diameter in the high-frequency region of the electrode Nyquist plot is smaller, indicating that the amorphous FeP obtained in Example 1 2 The electrode has a very small charge transfer resistance, which indicates that the amorphous FeP 2 Improved the conductivity of electrode materials.
[0079] Amorphous FeP obtained in Example 1 2 The CV curve of the electrode at a scanning rate of 0.1 to 2 mV / s is as follows Figure 7 As shown, the amorphous FeP obtained in Example 1 2 The corresponding log(i) vs.log(v) graph of the electrode is shown in Figure 8 As shown. Figure 7 The fitting and analysis show that the b values of the cathode and anode are 0.76 and 0.96, respectively, indicating that the amorphous FeP 2 Capacitance dominates lithium-ion storage in electrodes.
[0080] Amorphous FeP obtained in Example 1 2 The estimated pseudocapacitive contribution of the electrode at a scan rate of 2.0 mV / s is shown in the figure below. Fig. 9 As shown. Fig. 9 It can be seen that with the increase of scanning rate, amorphous FeP 2 The pseudocapacitive contribution in the electrode increased from 49% (scan rate 0.1 mV / s) to 82% (scan rate 2.0 mV / s).
[0081] Fig.10 Amorphous FeP 2 Contributions of pseudocapacitance and diffusion-controlled effects to the total charge storage of electrodes at different scan rates.
[0082] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing amorphous FeP2, characterized in that: The steps include: (1) hydrothermally reacting iron salt, urea and water to obtain an iron source precursor; (2) The iron source precursor and the phosphorus source are subjected to a phosphating reaction in a mixed gas to obtain amorphous FeP2.
2. The method for preparing amorphous FeP2 according to claim 1, characterized in that: The iron salt is ferric chloride hexahydrate.
3. The method for preparing amorphous FeP2 according to claim 2, characterized in that: The usage ratio of the iron salt, urea and water is 1 mol: 1-3 mol: 5-10 L.
4. The method for preparing amorphous FeP2 according to claim 1, characterized in that: In the step (1), the temperature of the hydrothermal reaction is 100 to 120° C., and the time of the hydrothermal reaction is 6 to 8 hours.
5. The method for preparing amorphous FeP2 according to claim 1, characterized in that: In the step (2), the phosphorus source is sodium hypophosphite; and the mass ratio of the iron source precursor to the phosphorus source is 1:10-25.
6. The method for preparing amorphous FeP2 according to claim 5, characterized in that: In the step (2), the phosphating reaction is carried out in a tubular furnace; the iron source precursor is located in the middle and downstream of the tubular furnace, the phosphorus source is located in the upstream of the tubular furnace, and the distance between the iron source precursor and the phosphorus source is 1 to 5 cm.
7. The method for preparing amorphous FeP2 according to claim 6, characterized in that: In the step (2), the mixed gas is a mixed gas of hydrogen and argon, the flow rate of the mixed gas is 400-500 cc / min, and the volume ratio of the hydrogen to argon is 10-20:80-90.
8. A method for preparing amorphous FeP2 according to any one of claims 5 to 7, characterized in that: In the step (2), the heating rate of the phosphating reaction is 2-4°C / min, the temperature of the phosphating reaction is 200-300°C, and the time of the phosphating reaction is 4-8h.
9. Amorphous FeP2 obtained by the method for preparing amorphous FeP2 according to any one of claims 1 to 8.
10. Use of the amorphous FeP2 according to claim 9 in lithium-ion batteries.
Citation Information
Patent Citations
Preparation method of iron phosphide nanosheet and biomass carbon composite material and application
CN108807941A
Method of producing iron phosphide, positive electrode for lithium secondary battery comprising iron phosphide, and lithium secondary battery comprising same
CN110998918A
Preparation method of self-supporting ferronickel phosphide composite nanosheet
CN111747388A
Preparation method of multi-channel surface modified amorphous iron oxide nanospheres
CN113979480A
Nitrogen-doped iron phosphide, preparation method thereof, negative electrode material, secondary battery and electric equipment
CN117088342A